Evaluation of Peaking Time Variation in Power Generation of a Cascaded Hydropower System: A Case Study of Arun River - Karn, Megha; Pandey, Vishnu Prasad; Basnyat, Divas B. (Journal of Engineering Issues and Solutions, 2025)
This study evaluates the energy generation performance of cascaded hydropower projects— Kimathanka Arun (KAHEP), Upper Arun (UAHEP), and Arun-4— three run-of-river projects in Nepal’s Arun River Basin under varying peaking time conditions. Using simulation data across dry (December–May) and wet (June–November) seasons, the study investigates hourly and daily energy patterns for peaking durations ranging from 4 to 12 hours. Results show that a 6-hour peaking duration most effectively aligns with morning and evening peak electricity demand in the dry season, maximizing energy benefit. Beyond 6 hours, the power generation at full capacity was restricted by the available design live storage (daily pondage) capacity. Although Arun-4 is designed as a run-of-river (RoR) project, it will benefit from peaking power generation due to upstream flow regulation from PRoR plants, underlining the advantages of coordinated cascade operations. In the wet season, generation remains stable—at full installed capacity—regardless of peaking time, due to abundant flow. The study suggests that optimizing installed capacity and live storage (daily pondage) capacity and designing PRoR plants for 4–12-hour peaking can improve dry season generation. Our analysis shows that the current design (live storage and installed capacity) of the two upstream PROR projects is suitable for a 6-hour peaking capacity. Policy recommendations include revising hydropower operation guidelines to incorporate coordinated peaking strategies, optimizing generation capacity, storage and system operation planning, and benefit-sharing mechanisms. With the increase of other variable renewable energy generation like wind and solar, a higher installed (peaking) capacity for a shorter peaking duration could be highly beneficial. These measures can significantly enhance power system reliability, generation mix and support Nepal’s growing power demands, particularly during critical dry periods.